A case of natalizumab-associated progressive multifocal leukoencephalopathy with repeated negative CSF JCV testing. (6th March 2013) - Mazda, Monica E.; Brosch, Jared R.; Wiens, Andrea L.; Bonnin, José M.; Kamer, Aaron P.; Mattson, David H.; Snook, Riley J.
<x xml:space="preserve">Abstract</x> The development of progressive multifocal leukoencephalopathy (PML) in patients treated with natalizumab is a well-known potential risk. Diagnosis of PML can be confounded in patients with multiple sclerosis (MS) if new demyelinating lesions develop, and the sensitivity of existing diagnostic tests is less than ideal. In the case presented here, four samples of cerebrospinal fluid tested negative for John Cunningham virus (JCV) DNA by polymerase chain reaction, yet brain biopsy eventually proved positive by immunohistochemistry. A review of the limitations of existing clinical diagnostic tests is addressed, and we review the most recent literature on the proper management of natalizumab-treated MS patients.